Cranfield DrivAer CAD_Pack_3 Mirrors - Francisco Soares, Renan; Garry, Kevin; Holt, Jenny (Cranfield University, 2018)
Mirrors CAD Pack (35% scaled-version), including:1. DrivAer - Mirrors (base plate only) (woM):DrivAer mirrors, base plate only.2. DrivAer - Mirrors (standard) (wM):DrivAer mirrors, standard version.CAD files available in IGS, STEP, STL, and Parasolid formats. All geometries are provided in [mm].Notation:(woM) = without external mirrors.(wM) = with external mirrors. --CAD designed and uploaded by:Renan F Soares - PhD in Aerospace Applied Aerodynamics Group Cranfield University, United Kingdom
Keywords: 'CAD'; 'DrivAer'; 'Automotive'; 'Aerodynamics'; 'Mirrors'; 'Aerodynamics (excl. Hypersonic Aerodynamics)'; 'Automotive Engineering not elsewhere classified'